The influence of price, brand ambassador, customer experience and customer trust on shopee user loyalty by using customer satisfaction as intervening variable - Felix Juliono; Yulianty Dewi; Ella Silvana Ginting; Apren Halomoan Hutasoit (Indonesia Accounting Research Journal, 2022)
This study aims to determine and analyze the influence of price, Brand Ambassador, Customer experience and customer trust towards Shopee user loyalty with customer satisfaction as an Intervening variable case study on Mikroskil University students. The type of data used is purposive sampling by determining the criteria for mikroskil students who have transacted at shopee and processing samples with the saturated method. The data testing method used is descriptive quantitative. The population in this study was 84 students at the University of Mikroskil ledger 2018 and 2019 and the sample was 84 students. The analysis showed that price, brand ambassador and customer trust have a significant effect on customer satisfaction while customer experience has no effect. Brand Ambassador and Customer Satisfaction have a significant effect on Customer Loyalty while Price, Customer Experience, Customer Trust have no effect. Price, Brand Ambassador and Customer Trust have an indirect effect on customer loyalty through customer satisfaction. Meanwhile, customer experience has a direct effect on customer loyalty. The results of the coefficient of determination 1 of 66.9% that the variable price, brand ambassador, customer experience and customer trust can explain the variable customer satisfaction and the results of the coefficient of determination 2 of 72.3% that the variable price, Brand Ambassador, Customer Experience, Customer trust and customer satisfaction can explain customer loyalty.